Serum heme oxygenase 1 (HO-1), soluble FMS like tyrosine kinase (sFlt-1) level, and neonatal outcome in early onset, late onset preeclampsia, and normal pregnancy - Muhammad Ilham Aldika Akbar; Mita Herdiyantini; Rozi Aditya Aryananda; Nareswari CIninta; Manggala Pasca Wardhana; Khanisyah Erza Gumilar; Budi Wicaksono; Ernawati; Agus Sulistyono; Aditiawarman; Hermanto Tri Joewono; Nadir Abdullah; et al. (Taylor & Francis Group, 2018)
Objective: To compare the level of serum heme oxygenase 1 (HO-1), soluble FMS like tyrosine kinase (sFlt-1), and neonatal outcome in early onset preeclampsia (EO-PE), late onset preeclampsia (LO-PE), and normal pregnancy (NP). Methods: In this prospective observational case control study, HO-1 and sFlt-1 levels were measured in blood samples within 24 h of hospital admission. Preeclampsia cases were divided into two groups based on gestational age at delivery: EO-PE (<34 weeks) and LO-PE (≥34 weeks). A total of 45 patients were involved in this study. Result: Maternal serum level of sFlt-1 was higher in EO-PE than LO-PE and NP groups (mean ± SD; 14.50 ± 17.12 ng/ml vs 5.20 ± 6.69 ng/ml vs 2.72 ± 1.2 ng/ml [p = 0.020]. Maternal serum level of HO-1 was not different between EO-PE, LO-PE, and NP groups (p = 0.681). Birthweights were significantly lower in the EO-PE group compared with the LO-PE and NP groups (1580 ± 536 g vs 2635 ± 578 g vs 3010 ± 371 g [p = 0.000]). The rate of small for gestational age infant (26.7% vs 6.7% vs 0%; p = 0.046) and perinatal death (20% vs 0 vs 0; p = 0.037) was also significantly higher in EO-PE compared to LO-PE and NP. The maternal sFlt-1 level was negatively correlated with birthweight (p = 0.006; CC = −0.445). Conclusion: This study did not find a correlation between maternal HO-1 levels and sFlt-1 levels. Maternal serum sFLt-1 levels in preeclampsia were higher in EO-PE and were associated with a worse perinatal outcome.